Funeral Rites in Contemporary Korea The Business of Death - Han, Gil-Soo.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book explores 21st century Korean society on the basis of its dramatically transforming and rapidly expanding commercial funeral industry. With insights into contemporary Confucianism, shamanism and filial piety, as well as modernisation, urbanisation, the division of labour and the digitalisation of consumption, it is the first study of its kind to offer a sophisticated, integrated sociological analysis of how the commodification of death intersects with capitalism, popular culture and everyday life in contemporary Korea. Through innovative analyses of funeral advertising and journalism, screen and literary representations of funerals, online media, consumer accounts of using funeral services and other sources, it offers a complex picture of the widespread effects of economic development, urbanisation and modernisation in South Korean society over the past quarter century. In the aftermath of the Korean "economic miracle" novel ways of paying respect to deceased kin have emerged;using Max Weber's concept of "pariah capitalism", Gil-Soo Han shows how the heightened obsession with and boom in the commodification of death in Korea reflects radical transformations in both capital and culture.
Chapter 1. Introduction -- Chapter 2. Literature review and theoretical perspectives -- Chapter 3. Economic, social and familial shifts in contemporary South Korea -- Chapter 4. An analysis of four movies dealing with funeral rites in Korea -- Chapter 5. Funeral and media-saturated world: An analysis of advertisements -- Chapter 6. The rise, fraud and fall of funeral service conglomerates: topics and concerns in investigative journalism -- Chapter 7. Grassroots concerns: an analysis of service user's bulletins boards -- Chapter 8. Ossuary: social class in the afterlife -- Chapter 9. Concluding remarks.
Keywords: Political sociology; Mass media; Ethnology -- Asia; Culture; Business; Asia; Motion pictures -- Asia; Political Sociology; Media Sociology; Asian Culture; Asian Business; Asian Film and TV